Practical Manual of Pharmacology for Medical Students - Badyal, D. Dinesh (Jaypee Brothers Medical Publishers, 2018)
This book has been written keeping in view the desired shift in the pharmacology practical teaching from pharmacy-based redundant experiments to more meaningful, clinically relevant problem-based exercises. The book covers all essential components to impart the necessary skills required to students in the subject of pharmacology as per prevailing regulations in the country. The book highlights the important skills to be imbibed by budding doctors which will aid in rational therapeutics. The book covers all feasible exercises in pharmacology. The book discusses all components of non-didactic lecture teaching in pharmacology. In fact, the 200 hours devoted to practical pharmacology in the UG curriculum includes seminars, group discussions, tutorials, innovative methods, etc. These components have been strengthened. The book also adds the practical components for BDS and MD students. Research has become an important issue for budding doctors now. In UG, they are now going for short research projects followed by thesis work in PG courses, so it has been included now. All the above additions are based on the feedback received from students, faculty and education experts.